Maintain Files Confidential By Using Rail Fence Cipher And Rot13 Method - Situmorang, Rantouli; Ikhsan, Muhammad; Hasugian, Abdul Halim (Bahasa Indonesia, 2023)
Transmission of information over long distances using internet media is faced with the problem of data security and confidentiality which is one of the important aspects of data communication, both for the purpose of data security and for individual privacy. One of the communication media is to use written text because a lot of information can be conveyed through writing (text) and sometimes in the text there is confidential information. Those who want their data not to be known by unauthorized parties always try to find ways to secure the information to be communicated. The Rail Fence Cipher algorithm has an advantage over other algorithms because in the process of writing plaintext into ciphertext it can be done on any line so that it adds to the complexity of the encryption and decryption process. The Rotate13 algorithm is a development of the Caesar cipher algorithm where this algorithm changes each letter character with 13 characters in front and one behind it according to the alphabet where the 13th character shift is carried out, namely the letter A is replaced with N. So that the data is disguised and cannot be read at a glance then shift the character in the ASCII table by shifting back as much as 13 characters. In this study, encryption and decryption were carried out by combining the Rail Fence Cipher algorithm with ROT13, where the encryption and decryption process is done 2 times. Based on the experimental results, the relationship between the encryption process time and the plaintext size shows that there is an effect of processing time speed based on the number of plaintext lengths in each algorithm and based on the relationship between the encryption process time and the decryption process time, it shows that the time used does not have a significant difference.